Medical Imaging 2005: Physics of Medical Imaging 2005
DOI: 10.1117/12.597317
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a photon-counting breast tomosynthesis imaging system

Abstract: Digital breast tomosynthesis promises solutions to many of the problems currently associated with projection mammography, including elimination of artifactual densities due to the superposition of normal tissues and increasing the conspicuity of true lesions that would otherwise be masked by superimposed normal tissue. We have investigated tomosynthesis using 45 photon counting, orientation sensitive, linear detectors which are precisely aligned with the focal spot of the x-ray source. The x-ray source and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 11 publications
(6 reference statements)
1
29
0
Order By: Relevance
“…This research found an increase in detectability with scan angle for all signal diameters greater than 500 m. Previous research found an improvement in depth resolution with increased scan angle. 15,18,41 Both results are equivalent because greater depth resolution results in higher signal contrast. This can be understood by considering the projections of a tomosynthesis volume acquired with different scan angles.…”
Section: Discussionsupporting
confidence: 58%
“…This research found an increase in detectability with scan angle for all signal diameters greater than 500 m. Previous research found an improvement in depth resolution with increased scan angle. 15,18,41 Both results are equivalent because greater depth resolution results in higher signal contrast. This can be understood by considering the projections of a tomosynthesis volume acquired with different scan angles.…”
Section: Discussionsupporting
confidence: 58%
“…The stationary case is the most common, but several prototype DBT systems have been built with a C-arm geometry as well (e.g. Ren et al, 2005;Maidment et al, 2005;Maidment et al, 2006). The present study is, to the best of our knowledge, the first in the DBT literature to present a direct comparison between the stationary and C-arm imaging geometries.…”
Section: Stationary Detector Versus C-arm Configurationmentioning
confidence: 96%
“…Such image normalisation is an important research area in itself (Tromans et al, 2008), and is beyond the scope of this paper. Following Zhou et al (2006), we assume attenuation coefficients at 30 keV, which is within the range reported in the literature (Wu et al, 2003;Ren et al, 2005;Bissonnette et al, 2005;Maidment et al, 2005;Maidment et al, 2006). We also assume an ideal photon-counting detector.…”
Section: Reference Systemmentioning
confidence: 98%
See 1 more Smart Citation
“…In order to improve contrast at reduced doses, photoncounting detectors have been considered in the search for alternatives to the conventional X-ray detectors used in radiography and CT [3][4][5].…”
Section: Introductionmentioning
confidence: 99%